Qualidade da educação: história e memória do ginásio estadual de Jaú (Jaú-SP, 1946-1961) - Machado, Rosinei Dias Gevezier Turbiani (2008)
In the present research, of historical nature, it was intended to study the secondary school teaching at the Secondary State School of Jaú, in the state of São Paulo, between the years of 1946 to 1961, considering the climax of the secondary school teaching expansion. Based on the references of analyses about educational institutions, and going over the memory field, this paper aims at the comprehension of how the secondary school teaching was organized in this institution, in a historical period marked by the apparent contradiction between the nature of the elite leaders makers of this teaching degree and the expansion process of the secondary school, and the comprehension of how the memory of a high-quality school was built. To talk about this theme, the school documents, periodicals and pictures were analyzed, besides registers of interviews with persons who took part in the history of the institution